Yes, There Is Deqi Sensation in Laser Acupuncture. (20th February 2013) - Litscher, Gerhard
Abstract : Deqi, a composite of unique sensations, is essential for clinical efficacy according to Traditional Chinese Medicine. It is described as a sensory perception of varying character and is mostly ascribed to metal needle acupuncture. However, it can also be elicited by different kinds of laser acupuncture stimulation. This short paper summarizes the current scientific status of deqi in laser stimulation. Different kinds of laser acupuncture are described in a comprehensive form, and the most interesting studies concerning deqi and laser acupuncture are presented.